Application of Fractional Calculus in the Dynamical Analysis and Control of Mechanical Manipulators - Ferreira, N. M. Fonseca (2019)
Mathematics Subject Classification: 26A33, 93C83, 93C85, 68T40Fractional Calculus (FC) goes back to the beginning of the theory of differential calculus. Nevertheless, the application of FC just emerged in the last two decades. In the field of dynamical systems theory some work has been carried out but the proposed models and algorithms are still in a preliminary stage of establishment. This article illustrates several applications of fractional calculus in robot manipulator path planning and control.